Effect of Turning Parameters on Tool Wear, Surface Roughness and Metal Removal Rate of Alumina Reinforced Aluminum Composite. (2016) - Bansal, Puneet; Upadhyay, Lokesh
Abstract: Now a day's demand of light materials is increasing continuously and MMC of aluminum playing a vital role to fulfill these demands due to their light weight, high strength and appreciable hardness etc. This study deals with the manufacturing of Aluminum based MMC of Alumina. Three samples were manufactured by sand casting with 2%, 4% and 6% of alumina by weight and mechanical properties like tensile Strength and Hardness were tested. Investigation reveals that mechanical properties enhanced in appreciable fashion as compared to pure aluminum. Turning on MMCs were carried out using uncoated carbide tool and coated tool. Turning test were performed at various speed, feed rate, depth of cut and percentage of alumina inclusion in MMCs. Furthermore tool wear, surface roughness and metal removal rate were investigated. Purpose of the study is to observe and understand the behavior of the turning parameters of composite materials under various operating conditions.